Effect of Tranexamic Acid on Coagulation and Fibrin Clot Properties in Children Undergoing Craniofacial Surgery - Fenger-Eriksen, Christian; Lindholm, Alexander D'Amore; Krogh, Lisbeth; Hell, Tobias; Berger, Martin; Hermann, Martin; Fries, Dietmar; Juul, Niels; Rasmussen, Mads; Hvas, Anne-Mette (Thrombosis and Haemostasis, 2020)
Objective Craniosynostosis surgery in small children is very often associated with a high blood loss. Tranexamic acid (TXA) reduces blood loss during this procedure, although the potential underlying coagulopathy in these children is not known in detail. Objective was to determine the nature of any coagulopathy found during and after craniosynostosis surgery and to characterize the effect of TXA on fibrin clot formation, clot strength, and fibrinolysis.Materials and Methods Thirty children received either TXA (bolus dose of 10 mg/kg followed by 8 hours continuous infusion of 3 mg/kg/h) or placebo. Dynamic whole blood clot formation assessed by thromboelastometry, platelet count, dynamic thrombin generation/thrombin-antithrombin, clot lysis assay, and fibrinogen/factor XIII (FXIII) levels were measured. Additionally, clot structure was investigated by real-time live confocal microscopy and topical data analysis.Results Increased ability of thrombin generation was observed together with a tendency toward shortened activated partial thromboplastin time and clotting time. Postoperative maximum clot firmness was higher among children receiving TXA. FXIII decreased significantly during surgery in both groups.Resistance toward tissue plasminogen activator-induced fibrinolysis was higher in children that received TXA, as evidenced by topical data analysis and by a significant longer lysis time. Fibrinogen levels were higher in the TXA group at 24 hours.Conclusion A significant coagulopathy mainly characterized by changes in clot stability and not parameters of thrombin generation was reported. Tranexamic acid improved clot strength and reduced fibrinolysis, thereby avoiding reduction in fibrinogen levels.
Keywords: antifibrinolytic agents; blood coagulation; craniosynostosis; fibrinolysis; hemorrhage